Efficient renaturation of inclusion body proteins denatured by SDS - He, C.; Ohnishi, K.
Inclusion bodies are often formed when the foreign protein is over expressed in Escherichia coli. Since proteins in inclusion bodies are inactive, denaturing and refolding of inclusion body proteins are necessary to obtain the active form. Instead of the conventional denaturants, urea and guanidine hydrochloride, a strong anionic detergent SDS was used to solubilize C-terminal His-tag form of ulvan lyase in the inclusion bodies. Solution containing SDS-solubilized enzyme were kept on ice to precipitate SDS, followed by SDS-KCl insoluble crystal formation to remove SDS completely. After removing the precipitate by centrifugation, the supernatant was applied to Ni-NTA column to purify His-tagged ulvan lyase. The purified protein showed a dimeric form and ulvan lyase activity, demonstrating that SDS-denatured protein was renatured and recovered enzyme activity. This simple method could be useful for refolding other inclusion body proteins.
Keywords: INCLUSION BODIES; REFOLDING; SDS; ULVAN LYASE